2007
DOI: 10.3769/radioisotopes.56.163
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Electron Beam Irradiated Crude Drugs by Electron Spin Resonance (ESR)

Abstract: Perillae Herba, Sennae Folium, Cinnamomi Cortex, Phellodendri Cortex, Ginseng Radix, Glycyrrhizae Radix, Paeoniae Radix, and Zingiberis Rhizoma were irradiated with electron beam (5 MeV) and organic radicals were detected by ESR measurement, before and after irradiation (10 kGy). A single line spectrum was detected at around g=2.005 in non-irradiated crude drugs, and radical concentrations were high in the leaf varieties of crude drugs. After irradiation, the signal intensity around g=2.005 increased, and a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…2.4 mT) are persistently present in the observed spectra. In contrast, the widths of singlet spectra near g = 2.005 observed in un-irradiated plant materials are around 1 mT (Yamaoki et al, 2007). Therefore, in plant materials that consist mainly of carbohydrates and contain more than 1% mono-or disaccharides (w/w dry), the emergence of major spectral components with a line width of ca.…”
Section: Identification Of Radical Components In Irradiated Gingersmentioning
confidence: 81%
See 2 more Smart Citations
“…2.4 mT) are persistently present in the observed spectra. In contrast, the widths of singlet spectra near g = 2.005 observed in un-irradiated plant materials are around 1 mT (Yamaoki et al, 2007). Therefore, in plant materials that consist mainly of carbohydrates and contain more than 1% mono-or disaccharides (w/w dry), the emergence of major spectral components with a line width of ca.…”
Section: Identification Of Radical Components In Irradiated Gingersmentioning
confidence: 81%
“…This observation is a characteristic of spectra observed in non-irradiated lightly pigmented root or rhizome drugs because the spectra near g =2.005 are considered to involve phenoxy radical signals derived from plant pigment such as polyphenol. We have found that the radical concentrations of non-irradiated peony root and ginseng root were lower than that of herb drugs containing anthocyanin, such as red pellila (Yamaoki et al, 2007). After EB irradiation, complex asymmetric spectra were observed in gingers.…”
Section: Esr Spectra Of Gingersmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, the two signals observed approximately 73 mT of the signal at g ¼ 2.005 were regarded to be derived from cellulose radicals, and assigned as part of the triplet spectrum (Raffi and Agnel, 1989). These signals have been previously determined in the irradiation of fruits, spices and medicinal herbs, and were observed in irradiated samples for a long time period (Korkmaz and Polat, 2001;Raffi and Agnel, 1989;Yamaoki et al, 2005Yamaoki et al, , 2007.…”
Section: Esr Spectra Of Fennelmentioning
confidence: 99%
“…ESR spectral characteristics similar to those of irradiated food containing crystalline sugars have been observed in irradiated samples (Yamaoki et al, 2007). In this study, the major ESR components of irradiated peony root were identified by spectral analysis, and the relationship between the ESR signal intensity and the sugar content was investigated.…”
Section: Introductionmentioning
confidence: 98%